Detection of aflatoxin B1 with a new label-free fluorescent aptasensor based on exonuclease I and SYBR Gold. Issue 22 (1st June 2020) - Guo, Zhijun; Lv, Lei; Cui, Chengbi; Wang, Yan; Ji, Shuang; Fang, Jiaqi; Yuan, Ming; Yu, Hansong
Abstract : This paper describes a new label-free fluorescent aptasensor for the detection of aflatoxin B1 (AFB1 ) based upon exonuclease I (Exo I) and SYBR Gold, in which SYBR Gold, aptamer, AFB1, and Exo I were used. Abstract : This paper describes a new label-free fluorescent aptasensor for the detection of aflatoxin B1 (AFB1 ) based upon exonuclease I (Exo I) and SYBR Gold, in which SYBR Gold, aptamer, AFB1, and Exo I were used. Specific combinations of aptamer and AFB1 occurred in the presence of AFB1 and consequently altered the spatial structure of the aptamer, thereby preventing its digestion by Exo I. When SYBR Gold was added, intense fluorescence was observed. Additionally, a good linear relationship was observed under optimized conditions between the fluorescence intensities and the AFB1 concentrations ( R 2 = 0.993). The established aptamer sensor was highly sensitive and exhibited a low limit of detection of 1.82 ng mL −1, with superior specificity for AFB1 . It was also used in the quantification of AFB1 levels in soybean sauce samples and demonstrated satisfactory recoveries in the scope of 94.8–108.9%. The proposed sensor is highly sensitive, low cost, and capable of rapid detection and can thus be used to determine mycotoxin levels in a wide range of feeds and food products in a high-throughput and quantitative means.